Pengaruh Persepsi Manfaat, Hedonic Motivation terhadap Penerimaan dalam Niat Gabung Membership Gym di Semarang - Harmanda Berima Putra; Wisna Rizki Ramadan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the effect of perceived benefits and hedonic motivation on the intention to join gym membership in Semarang. The research method used is a quantitative method. The data collection method used is an online quetioner survey with a questionnaire. The research sample is gym consumers in Semarang with a sample size of 151 people. The results of the SEM analysis using SMART PLS software show perceived benefits and hedonic motivation is proven to have a positive effect on the intention.